Testing a novel sonar‐based approach for measuring water depth and monitoring sediment storage in beaver ponds. (23rd November 2022) - Bradbury, Gareth; Puttock, Alan; Coxon, Gemma; Clarke, Stewart; Brazier, Richard E.
Abstract: Widely available 'fish‐finder' echo‐sounding devices are beginning to be used in bathymetric studies to estimate geomorphic change. To date, however, there have been no applications in shallow and complex wetlands, where changes in sediment storage are notoriously dynamic in time and difficult to describe accurately in space. Therefore, in this study, we tested the performance of an 'off‐the‐shelf' fish‐finder for mapping bathymetry in a shallow beaver pond. We tested fish‐finder sonar depth readings against a traditional‐sounding lead‐line method across 21 paired Sampling Points with a minimum depth of 0.31 m and a mean of 0.65 m. Spatial accuracy of the unit was also tested against a differentially corrected Global Navigation Satellite System (GNSS) receiver. Measured depths to pond bottom from the fish‐finder were on average within 5%, although significantly 0.015 m ( SD  = 0.034) less than those obtained by the lead‐line method. Spatial accuracy, however, varied greatly compared to the corrected GNSS receiver readings, with a mean discrepancy of 2.7 m ( SD  = 1.5) but up to 6.2 m. Given the close match of depth readings between the two methods, we conclude that sonar is a suitable, cost‐effective, and less‐intrusive method than existing techniques, even in moderately vegetated shallow waterbodies. Methods do need to be adopted to account for poor spatial precision with 'off‐the‐shelf' fish‐finder models, but this can be rectified with survey design or using a secondary GNSS. Application of this technology will allow rapid one‐off surveys or repeated monitoring of depth, bedform and sediment accumulation in otherwise hard‐to‐access or disturbance‐sensitive wetlands, such as beaver ponds and water treatment or flow attenuation wetlands.